Key technologies of symbiotic transmission for 6G Internet of things - Mingjiang WU; Xianfu LEI; Li LI; Xiaohu TANG (物联网学报)
mMTC (massive machine-type communication) is one of the three major application scenarios of 5G network,but it is highly likely that the truly mature Internet of everything may not be realized until the future 6G network.In order to realize the deep immersive ubiquitous connection network,6G IoT will simultaneously provide all-round services such as high data rate,low latency,high reliability and massive connections.Firstly,the 6G was prospected and the technical challenges of 6G IoT were summarized.Then the existing physical layer transmission technologies of IoT were reviewed.Next,the promising symbiotic transmission technologies for 6G IoT were introduced and discussed,which enable the possibility that active transmission and passive transmission facilitates each other and provide a new solution for 6G IoT transmission.Finally,some possible future research directions were presented for symbiotic transmission in 6G IoT.